The Role of Purchase Intention in Mediating the Impact of Environmental Concern on the Purchase of Eco-Friendly Products - Dina, Jihan Farah; Kuswati, Rini; Soepatini, Soepatini (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to analyze the role of purchase intention in mediating the influence of environmental concern on the purchase of environmentally friendly products. The method used in this study is quantitative. The population and sample in this study are the general public in Indonesia who have a minimum education in high school and understand environmentally friendly products. The sample size in this study was 200 respondents. The data source used in this study is primary data. The measurement scale used in this study is a 5-point Likert scale. Data analysis using SmartPLS version 3.0. The results of the analysis in this study indicate that environmental concern has a significant positive effect on purchase intention, environmental concern has a significant positive effect on purchasing behavior, purchase intention has a significant positive effect on purchasing behavior and purchase intention positively mediates environmental concern on purchasing behavior.